Responsabilidad social empresarial y el desempeño financiero en las mejores empresas para trabajar de un mercado emergente - Ostos, Jhony (2020)
Corporate social responsibility programs are increasingly valued by customers, however their financial justification in organizations is still limited. The design of this research was based on a qualitative study of comparative cases between the best companies to work in Peru (Great place to work - GPTW) in the period 2015-2017. The social responsibility practices and the financial results obtained from each were examined. The results indicate that there is a tendency for companies that execute social responsibility programs to obtain positive financial results at the same time.